Growth performance and meat quality of suckling beef calves as affected by alpine pasture topography - Gangnat I.D.M.; Kreuzer M.; Dufey P.-A.; Leiber F.; Berard J. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Summer alpine pastures have a heterogeneous topography. Since beef cattle walk long distances for grazing pasture slope could affect both physical activity intensity and energy expenditure, which may further affect muscle metabolism and meat quality. The present experiment investigated the effect of slope inclination on growth performance and meat quality under high-altitude conditions. Two groups of 12 Angus-sired suckling calves each were kept with their dams on summer alpine pastures (2000 m a.s.l.) either on a terrain with steep inclination (S) or on a flat terrain (F) for 2 months. Then, calves were slaughtered and meat quality was assessed on the longissimus dorsi (LD) and the biceps femoris (BF) muscles after 21 days of ageing. Average daily gains were lower in S-compared with F-calves (1.21 vs 1.35 kg/day; P<0.01), but live weights did not differ significantly between groups at slaughter (277 ± 24 kg). Carcass classification and carcass weight did not differ between groups. Shear force of BF was lower in S- than in F-calves (24.5 vs 27.5 Newton; P<0.05). Colour of LD tended to be brighter (37.2 and 36.4; P<0.09) and more yellow (1.44 and 0.51; P<0.07) in S- than F-calves; all other measurements showed no difference between S- and F-calves.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)